HUBUNGAN ANTARA MOTIVASI DENGAN KINERJA KADER POSYANDU Studi Observasi Analitik Kader Posyandu di Wilayah Kerja Puskesmas Bangetayu Kota Semarang - Zhafira Althafa Eka Atmaja; Purwito Soegeng Prasetijono (PT. Hasba Edukasi Mandiri, 2026)
The performance of posyandu cadres plays a crucial role in the success of maternal and child health services. Work motivation is one of the factors associated with cadre performance. This study aimed to analyze the relationship between motivation and the performance of Posyandu cadres in the working area of Bangetayu Public Health Center, Semarang City. This study used an analytic observational design with a cross sectional approach and consecutive sampling technique. Motivation was measured based on Herzberg’s Two Factor Theory. Data were collected using a validated and reliable questionnaire. Data analysis was conducted using univariate and bivariate methods with Spearman’s Rho correlation test. The results showed that 42.1% of cadres had good motivation, 42.1% had moderate motivation, and 15.8% had low motivation. Cadre performance was categorized as good in 34.2% of respondents, moderate in 34.2%, and low in 31.6%. The correlation test showed a p value < 0.001 with a correlation coefficient of r = 0.580. The relationship was positive with moderate strength. This study concludes that motivation has a positive and moderate relationship with the performance of posyandu cadres in the working area of Bangetayu Public Health Center, Semarang City.